High-Temperature, Nonradioactive Primer Extension Assay for Determination of a Transcription-Initiation Site. (July 1998) - Yamada, M.; Izu, H.; Nitta, T.; Kurihara, K.; Sakurai, T.
We have developed a simple and safe method for the determination of a transcription-initiation site. In this method, reverse transcriptase of the avian myeloblastosis virus or r Tth DNA polymerase from Thermus thermopilus was used with a fluorescein isothiocyanate (FITC)-labeled primer. The primer-extension reaction can be performed at a high temperature, which reduces the hindering effect of the secondary structure in RNA, and can omit the annealing step between RNA and the primer. Almost all steps can be done in one tube. This procedure can provide reliable and reproducible data when compared with the conventional procedure at low temperature. Moreover, the sequencing ladder that is required for determining the position of extended products can be obtained with the same FITC-labeled primer.